Peran Taman Pendidikan Al-Quran (TPA) dalam Mengembangkan Kemampuan Membaca Al-Quran bagi Peserta Didik - Suharyani Suharyani (Jurnal Paedagogy, 2018)
Al-Qur'an Education Park is an Islamic education and teaching institution outside of school or it can be referred to as non-formal education for elementary school age children (aged 7-12 years), which educates students to be able to read the Koran well. and true according to the science of recitation as the main target. The objectives of this study were (1) To determine the role of the Al-Qur'an educational garden in improving the students' reading skills of the Al-Qur'an in Keling Hamlet, Kalijaga Tengah Village. (2) To find out the obstacles faced by the Al-Qur'an educational park in improving the students' reading skills of the Al-Qur'an in Keling Hamlet, Kalijaga Tengah Village. This research was conducted using a qualitative descriptive approach, the researcher became an instrument. The research used a qualitative approach because the problems discussed were not related to numbers, but described, described and described the role of the Al-Qur'an education garden in developing students' reading skills of the Koran in Keling Hamlet, Kalijaga Tengah Village, Aikmel Tahun District. 2014. From the results of this study, it can be explained that the role of the educational garden of the Al-Qur'an Raudatul Iman Dusun Keling is quite good. The Qur'an properly and correctly corresponds to the tartil. As for the obstacles faced by TPA in teaching reading the Qur'an, many students do not enter if there are activities / events in the community, inadequate facilities, this causes the learning process to be less than optimal, and a lack of educators.